2014
DOI: 10.1111/iep.12108
|View full text |Cite
|
Sign up to set email alerts
|

Induction and treatment of anergy in murine leprosy

Abstract: Leprosy is a disease consisting of a spectrum of clinical, bacteriological, histopathological and immunological manifestations. Tuberculoid leprosy is frequently recognized as the benign polar form of the disease, while lepromatous leprosy is regarded as the malignant form. The different forms of leprosy depend on the genetic and immunological characteristics of the patient and on the characteristics of the leprosy bacillus. The malignant manifestations of lepromatous leprosy result from the mycobacterial-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…2 . Quantitation of bacilli was achieved using IMAGE J software and the units were given in pixels 12 . Measurements were performed on 4-μm paraffin sections stained for acid-fast bacilli (Ziehl-Neelsen).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 . Quantitation of bacilli was achieved using IMAGE J software and the units were given in pixels 12 . Measurements were performed on 4-μm paraffin sections stained for acid-fast bacilli (Ziehl-Neelsen).…”
Section: Resultsmentioning
confidence: 99%
“…The progressive decrease in cell-mediated immunity, CMI (anergy), is characteristic of chronic infectious diseases produced by pathogenic mycobacteria 12 , 29 , 30 . Here, we showed that infection of mice with Mycobacterium lepraemurium ( MLM ) led to a disseminated, multiorgan, infection that did not directly affect CNS 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En un modelo experimental murino de lepra, la mejoría clínica de los animales infectados y tratados con EDL se evidenció con la reducción en la extensión y número de bacilos en los granulomas, así como en el desarrollo de tejido de granulación, indicativo de mejoría clínica, la cual fue mayor en los ratones que recibieron EDL combinado con bactericidas. 10,11 En el paciente descrito, al igual que en el modelo murino, se redujo el tamaño de los nódulos y la sintomatología clínica. Además, se registraron cambios en la citometría que sugieren reforzamiento del perfil Th1: se incrementaron los linfocitos CD4 y las células NK y se redujeron levemente las CD19.…”
unclassified